Human factors–based risk analysis to improve the safety of doffing enhanced personal protective equipment - Gurses, Ayse P.; Dietz, Aaron S.; Nowakowski, Elaine; Andonian, Jennifer; Schiffhauer, Maggie; Billman, Carrie; Abashian, Anya M.; Trexler, Polly; Osei, Patience; Benishek, Lauren E.; Xie, Anping; Pronovost, Peter; et al. (Infection control and hospital epidemiology, 2019)
To systematically assess enhanced personal protective equipment (PPE) doffing safety risks. We employed a 3-part approach to this study: (1) hierarchical task analysis (HTA) of the PPE doffing process; (2) human factors-informed failure modes and effects analysis (FMEA); and (3) focus group sessions with a convenience sample of infection prevention (IP) subject matter experts. A large academic US hospital with a regional Special Pathogens Treatment Center and enhanced PPE doffing protocol experience.ParticipantsEight IP experts. The HTA was conducted jointly by 2 human-factors experts based on the Centers for Disease Control and Prevention PPE guidelines. The findings were used as a guide in 7 focus group sessions with IP experts to assess PPE doffing safety risks. For each HTA task step, IP experts identified failure mode(s), assigned priority risk scores, identified contributing factors and potential consequences, and identified potential risk mitigation strategies. Data were recorded in a tabular format during the sessions. Of 103 identified failure modes, the highest priority scores were associated with team members moving between clean and contaminated areas, glove removal, apron removal, and self-inspection while preparing to doff. Contributing factors related to the individual (eg, technical/ teamwork competency), task (eg, undetected PPE contamination), tools/technology (eg, PPE design characteristics), environment (eg, inadequate space), and organizational aspects (eg, training) were identified. Participants identified 86 types of risk mitigation strategies targeting the failure modes. Despite detailed guidelines, our study revealed 103 enhanced PPE doffing failure modes. Analysis of the failure modes suggests potential mitigation strategies to decrease self-contamination risk during enhanced PPE doffing.